Weed Diversity, Biomass and Micronutrient Assessments on Peat Land Oil Palm Cultivation by Smallholders - Farah Syamimi, Basrol (Universiti Malaysia Sarawak (UNIMAS), 2017)
The relationship of crops, weed and micro nutrients in soil is essentially well understood in order to achieve good management and satisfactory crop production. The nutrients, soil and weeds composition in the two, four, and seven year old oil palm plantation by smallholders were studied at Melur Gemilang Plantation in Gedong, Samarahan area. The diversity index and dominance of weed species were calculated using Shannon-Wiener Diversity Index (H ') and Summed Dominance Ratio (SDR) respectively. The biomass and carbon stock estimation of weed species were also being assessed. Inductively coupled plasma mass spectroscopy (ICP-MS) technique was used to obtain the micro nutrients status of peat soil and weed samples. A total of 48 weed diversity was recorded in the two year - old planting area, followed by 23 and 13 weed species in the four and seven year - old oil palm cultivated area respectively. The selected species of Asystasia intrusa and Nephrolepis bisserata were analyzed for its micro nutrients content while the distribution of micronutrients deficit of oil palm were recorded using GPS device. H' value of 2.34 was recorded with the highest estimated carbon stock amount of 5.00 tonslha in two years old oil palm planted area. There were no significant differences showed between the variables ofmicronutrients with different depth of peat soil. Boron, zinc and copper were able to be detected in weed species while none in peat soil samples. The oil palm trees distribution of nutrients deficiency were greater at the younger oil palm than the older oil palm with generally deficient in copper, boron and zinc. Poor maintenance activities, peat soil micronutrient problems and low organic material decomposition rate in which different area of soil samples collected act as barriers for optimum oil palm yield. In order to provide valuable material for smallholder planters of oil palm plantations, efficient alternative is hopefully achieved through this study to supply required micro nutrients content for maximizing yield production cultivated on peat land. A iii proper micro nutrients application schedule and awareness of precautions on cultivation on peat land is important to prevent concern over disruption of peat land ecosystem.